Perempuan Dan Pernikahan Sirri Di Kalangan Mahasiswa Sekolah Tinggi Agama Islam Negeri Jember: Women and Unregistered Marriages Among Students of the State Islamic College of Jember - Hidayati, Titiek Rohanah (Fenomena, 2002)
The practice of unregistered Islamic marriage (nikah sirri) among university students continues to pose serious legal and gender-based challenges in contemporary Indonesia, particularly within Islamic higher education contexts. Drawing on gender analysis theory and Islamic family law frameworks, this study investigates students’ perceptions, motivations, and consequences of sirri marriage at STAIN Jember. The research aims to identify students’ attitudes toward sirri marriage, describe their motivations for entering such unions, and analyze responses to marital failure. Using a descriptive qualitative survey design with purposive sampling, data were collected from 89 students across three faculties through questionnaires, interviews, and documentation. Findings reveal that the majority of male students support sirri marriage, citing reasons such as reducing sin, cohabiting with partners, and financial unpreparedness, while female students report significantly higher perceived disadvantage. Most female respondents feel harmed by sirri marriage failure, yet most male students do not recognize this harm. Both genders largely agree on the necessity of registering sirri marriages with the Religious Affairs Office. The study concludes that gender awareness remains critically low among male students. Recommendations include integrating pre-marital education, family law literacy, and gender equality training into university curricula. Praktik pernikahan sirri di kalangan mahasiswa terus menimbulkan tantangan hukum dan gender yang serius di Indonesia kontemporer, khususnya di lingkungan perguruan tinggi Islam. Berdasarkan teori analisis gender dan hukum keluarga Islam, penelitian ini mengkaji persepsi, motivasi, dan konsekuensi pernikahan sirri di kalangan mahasiswa STAIN Jember. Penelitian bertujuan mengidentifikasi sikap mahasiswa terhadap pernikahan sirri, mendeskripsikan motivasi mereka, serta menganalisis tanggapan terhadap kegagalan pernikahan. Menggunakan desain survei kualitatif deskriptif dengan purposive sampling, data dikumpulkan dari 89 mahasiswa melalui angket, wawancara, dan dokumentasi. Hasil menunjukkan mayoritas mahasiswa laki-laki mendukung pernikahan sirri dengan alasan mengurangi dosa, tinggal serumah dengan pasangan, dan ketidaksiapan finansial, sementara mahasiswi menyatakan tingkat kerugian yang jauh lebih tinggi. Sebagian besar responden perempuan merasa dirugikan oleh kegagalan pernikahan sirri, namun mayoritas laki-laki tidak mengakui kerugian tersebut. Kedua jenis kelamin umumnya sepakat perlunya mencatatkan pernikahan sirri ke KUA. Penelitian menyimpulkan bahwa kesadaran gender di kalangan mahasiswa laki-laki masih sangat rendah. Rekomendasi mencakup integrasi pendidikan pranikah, literasi hukum keluarga, dan pelatihan kesetaraan gender ke dalam kurikulum universitas.